Effect of Environmental Factors on Job Performance among Nurses of Tertiary Health Care Sector: LMRJ - Akram, Tehseena (LIAQUAT MEDICAL RESEARCH JOURNAL, 2020)
To assess the eect of environmental factors on job performance among nurses of tertiary health care sector. A cross-sectional study was conduct to reply the learn questions. From side to side suitable variety, 200 nurses were selected from Services Hospital Lahore. Evocative and inferential data were worn for facts study. Signify and usual deviation were compute for regular variables and extent were computed for resounding variables. Both in the Pearson correlation and regression the environmental factors and job performance have the strong positive relationship with the p value <.001. is study reveals that the physical environment plays the important role on job performance which is already cited in literature the retention of the sta. Material surroundings of a physical condition-worry capability aects tremendously on the performance of the workers. is study suggests that performance may be improved by addressing safety, infection control measures, and environment temperatures and supplies availability.